2021
DOI: 10.1016/j.heliyon.2021.e06624
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the American Joint Committee on Cancer (AJCC) 8th edition tumor, node, metastasis (TNM) staging system on outcomes of differentiated thyroid cancer in Thai patients

Abstract: Background: In 2018, the American Joint Committee on Cancer (AJCC) 8 th edition (AJCC8) was introduced to replace the previous version (AJCC7) due to superiority of AJCC8 over AJCC7 for better prediction of survival from thyroid cancer. Aim: To compare AJCC staging systems with the American Thyroid Association (ATA) risk classification for the prediction of 5-year disease-free survival (DFS), and 5-year disease-specific survival (DSS) in Thai patients. Methods: We retrospectively reviewed all patients with his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Although the TNM classification was created to evaluate mortality in patients with DTC, it is worth noting that in the present study, a significantly higher proportion of patients with structural persistence was observed in SIII TNM8 compared to TNM7, as also demonstrated by Thai research [ 12 ] These findings can be explained by the fact that all tumors with gross local extension were eventually downstaged from SIV.…”
Section: Discussionsupporting
confidence: 63%
“…Although the TNM classification was created to evaluate mortality in patients with DTC, it is worth noting that in the present study, a significantly higher proportion of patients with structural persistence was observed in SIII TNM8 compared to TNM7, as also demonstrated by Thai research [ 12 ] These findings can be explained by the fact that all tumors with gross local extension were eventually downstaged from SIV.…”
Section: Discussionsupporting
confidence: 63%
“…[21] Our previous study also confirmed that a 5-year disease-specific survival was 98.7% in patients with American Joint Committee on Cancer 8th edition stages I. [22] Complications from RAI and TSH suppression therapy have received less attention than surgical complications due to the longer temporal relationship between exposure and development of adverse events. The primary goal of DTC treatments is to ensure the most effective and least invasive treatment and reducing the risk of persistent/recurrent disease.…”
Section: Discussionmentioning
confidence: 61%
“…Growing lines of studies and the latest American Joint Committee on Cancer staging system for differentiated thyroid carcinoma have indicated that the cut-off value of age at diagnosis used for staging increasing from 45 to 55 can allow low-risk patients to avoid aggressive surgical resections and postoperative therapies, improve disease management strategies, and reduce psychosocial and financial burdens ( Mazurat et al, 2013 ; Amin et al, 2017 ; Pontius et al, 2017 ; Kim et al, 2018 ; Shteinshnaider et al, 2018 ; Thewjitcharoen et al, 2021 ). That is, when the age at diagnosis exceeds 55, the overall prognosis worsens because of the increased cause-specific mortality in patients with PTC, and the mechanisms underlying this phenomenon remain elusive.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely acknowledged that age at diagnosis is a self-contained element of danger for the outcome of PTC patients ( Kim et al, 2017 ; Kauffmann et al, 2018 ). The cutoff value of age at diagnosis increased from 45 to 55 years, which is one of the most prominent features of the AJCC 8th staging system for judging the prognosis of individuals with differentiated thyroid carcinoma, allowing surgeons to better stratify patients to avoid radical surgical procedures and postoperative treatments ( Amin et al, 2017 ; Thewjitcharoen et al, 2021 ). Furthermore, one study combined clinical data with genetic data (differential gene expression, copy number variation, classical pathway alteration, and somatic mutation) and discovered that this current version for thyroid cancer can predict the recurrence rate and survival more accurately compared with the previous version ( Kim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%